Accumulated X-ray irradiation induces miR-187-5p upregulation mediating fibrotic buccal mucosal fibroblasts activities via DKK2 - Gang Zheng; Shuiqing Xu (Elsevier, 2023)
Background/purpose: With the wide application of X-rays in dental examinations, it is necessary to assess its potential risk and explore an effective indicator. This study aimed to analyze the response of miR-187-5p to X-ray irradiation and to evaluate its potential of predicting X-ray potential dangers. Materials and methods: Patients that had to receive dental X-ray examination were enrolled and the expression of miR-187-5p in the buccal mucosa swabs were detected by real-time quantitative polymerase chain reaction (PCR). The effect of miR-187-5p on fibrotic buccal mucosal fibroblasts (fBMFs) activities was assessed by cell migration and invasion and the expression of fibrosis markers. In mechanism, the interaction between miR-187-5p and DKK2 and their co-regulatory effects were also estimated. Results: Significant upregulation of miR-187-5p was observed in the patients who received over twice X-ray irradiation. miR-187-5p was found to regulate the luciferase and expression level of DKK2 in fBMFs. Moreover, miR-187-5p knockdown dramatically suppressed the migration and invasion of fBMFs and inhibited the expression of α-SMA, collagen I, and collagen II, three typical fibrosis markers. Silencing could reverse the inhibitory effect of miR-187-5p knockdown on fBMFs activities. Conclusion: Accumulated X-ray irradiation could induce miR-187-5p upregulation, which could regulate the fBMFs activities via modulating DKK2. miR-187-5p could serve as an indicator of X-ray examination dangers to prevent the potential risk during the accumulated application of X-ray irradiation in the dental examination.